Management Information Systems, Transformational Leadership, and Work Discipline Influenced the Work Effectiveness among Nurses: A Cross-sectional Study - Haryanto, Dedi; Hutapea, Fresley; Wahidi, Kemala Rita (International Journal of Nursing and Health Services (IJNHS), 2024)
Objective: The study aimed to determine the association between information management system, transformational leadership on working effectiveness with work discipline as intervening variables. Method: A cross-sectional study with a survey approach was conducted in this study. The data analysis was conducted using the path analysis. One hundred thirty-one samples were recruited in this study. Result: The results of this research show that the Management Information System has a significant effect on work effectiveness. Transformational leadership has a significant effect on work effectiveness. Management Information Systems have a significant effect on work discipline. Transformational leadership has a significant effect on work discipline. Work discipline has a significant effect on work effectiveness. Work discipline plays a significant role as an intervening agent between the Management Information System and work effectiveness or it could be said that the Management Information System has a significant effect on work effectiveness with work discipline as an intervening variable. Conclusion: Work discipline plays a significant role as an intervening agent between transformational leadership and work effectiveness or it can be said that transformational leadership has a significant effect on work effectiveness with work discipline as an intervening variable. Recommendation: The management level in the hospital need to consider the effective management information system and work discipline to improve working effectiveness. The transformation leadership was effective to increase motivation among employee so that the organization need to consider. Further study may develop the R&D study to develop the program focused on the working effectiveness and working efficiency to improve the level of hospital